Longitudinal Performance of Senescence Accelerated Mouse Prone-Strain 8 (SAMP8) Mice in an Olfactory-Visual Water Maze Challenge - Lam, Virginie; Takechi, Ryusuke; Albrecht, Matthew A.; D'Alonzo, Zachary John; Graneri, Liam; Hackett, Mark J.; Coulson, Stephanie; Fimognari, Nicholas; Nesbit, Michael; Mamo, John C. L. (Frontiers in Behavioral Neuroscience, 2018)
Morris water maze (MWM) is widely used to assess cognitive deficits in pre-clinical rodent models. Latency time to reach escape platform is frequently reported, but may be confounded by deficits in visual acuity, or differences in locomotor activity. This study compared performance of Senescence Accelerated Mouse Prone-Strain 8 (SAMP8) and control Senescence Accelerated Mouse Resistant-Strain 1 (SAMR1) mice in classical MWM, relative to performance in a newly developed visual-intramaze water pool testing protocol. Performance indicated as the escape time to rescue platform for classical MWM testing showed that SAMP8 mice as young as 6 weeks of age did poorly relative to age-matched SAMR1 mice. The visual-olfactory maze challenge described better discriminated SAMP8 versus SAMR1 mice than classical MWM testing, based on latency time measures. Consideration of the distance travelled rather than latency time in the classical MWM found no treatment effects between SAMP8 and SAMR1 at 40 weeks of age and the visual-olfactory measures of performance confirmed the classical MWM findings. Longitudinal (repeat) assessment of SAMP8 and SAMR1 performance at 6, 20, 30 and 40 weeks of age in the visual-olfactory testing protocol showed no age-associated deficits in SAMP8 mice to the last age end-point indicated. Collectively, the results from this study suggest the olfactory-visual testing protocol may be advantageous compared to classical MWM as it avoids potential confounders of visual impairment in some strains of mice and indeed, may offer insight into cognitive and behavioural deficits that develop with advanced age in the widely used SAMP8 murine model.